Zasiłek macierzyński z ubezpieczenia społecznego rolników - Puślecki, Damian (Wydawnictwo Naukowe UAM, 2014)
Maternity benefit payable from farmers social insurance S u m m a r y The aim of the deliberations presented in the paper was to establish the extent of protection due to an insured farmer in the event of a birth of a child requiring the mother to (temporarily) refrain from work. The subject of insurance protection as well as its financing and the quality of received benefits is being examined. The author concludes that the currently binding construction of maternity insurance does not provide a full cover of the insured person and is not fit for individuals engaged in agricultural activity, as it is isolated from the essence of the insurance itself, the insured subject, and the very function of social insurance. There is a clear need for isolating the maternity insurance in insurance law pertaining to farmers, their insurance cover, level of premiums paid, and the benefits granted. Maternity benefits in agriculture, being periodical payments, should have a compensatory- supportive function arising from the specifics of the work performed by those involved in agricultural activity.

L’indennità di maternità derivante dall’assicurazione sociale degli agricoltori R i a s s u n t o L’obiettivo delle considerazioni è di determinare la portata della tutela accordata all’agricoltore assicurato per la nascita del figlio e il sorgere della necessità di astenersi dal lavoro. Da questo punto di vista, l’autore analizza l’oggetto della tutela assicurativa e il suo campo di applicazione, nonché la questione del finanziamento e la qualità delle prestazioni ottenute. In conclusione, l’autore afferma che l’attuale strutturazione dell’assicurazione di maternità non garantisce la tutela dovuta agli assicurati e non trova giustificazione nell’attività agricola. Essa è completamente staccata dalla natura, dall’oggetto della tutela assicurativa e dalla funzione delle assicurazioni sociali. Vi è una chiara necessità di distinguere l’assicurazione di maternità nella legge sulle assicurazioni, determinare la portata della copertura assicurativa, ricalcolare i contributi versati dagli agricoltori e migliorare la qualità delle prestazioni. L’indennità di maternità in agricoltura, come prestazione temporanea.